(untitled) (Revista ABRA, 2019)
The city of Mar del Plata concentrates the sun and beach tourism of the General Pueyrredon party (Argentina). However, there are other natural landscapes of lagoon or mountain type in the territory, whose tourist offer is still weak. The general objective of the research is making a diagnosis of the tourist value of different landscapes. For this, they identify Landscape Units, their degree of environmental protection and the presence and possibility of tourist use. The putting in value tourist of other landscapes, beyond the coast, can contribute to decompress the pressure on the coasts and diversify the tourist-recreational offer, reducing the problems of seasonality of the destination. In virtue of a tourism development based on the conservation of these landscapes, problems of accessibility, infrastructure and equipment become important; and the strengthening of environmental protection.